ANALISIS STRATEGI PEMASARAN INTERNASIONAL PADA PRODUK REVOLUZIO (Studi pada PT Beon Intermedia) - Nugrahanti Khairani Aisyah; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
PT Beon Intermedia is company engaged in the field of ICT (information and communication technology. Based on preliminary observations conducted by researchers in the field, Revoluzio is an innovative e-business to implement automation in digital marketing. This product is an innovative e-business the most and become the only one, both Indonesia and abroad, so the company should also establish appropriate strategy for the international market. The aim of this study was to describe the changes in the factor analysis business so it appears the product revoluzio and explain the implementation strategy of STP on PT Beon Intermedia. The method used in this research is qualitative method with descriptive analysis. The results showed factor of the change in the business so that the product appears revoluzio among others 1)customers who expect extra value, experience, expert information, electronic solution, and empowerment;2)company;3)competition;4)collaboration;5)change. While the implementation of the strategy STP, segmentation product Revoluzio is the owner of the business at the age of 25 years or more who are ready to do business online in the era of digital marketing on the territory of Indonesia and the United States, targeting products Revoluzio is a business and product positioning Revoluzio is an all-in-one digital business. Keyword : marketing strategy, e-business, digital marketing, Revoluzio ABSTRAK PT Beon Intermedia adalah sebuah perusahaan yang bergerak di bidang ICT (information and communication technology. Berdasarkan observasi awal yang dilakukan peneliti di lapangan, Revoluzio merupakan inovasi e-business yang menerapkan automasi digital marketing. Produk ini merupakan inovasi e-business terbaru dan menjadi satu-satunya, baik di Indonesia maupun luar negeri, sehingga perusahaan juga harus menetapkan strategi yang tepat untuk pasar internasional. Tujuan dari penelitian ini adalah untuk menjelaskan analisa faktor perubahan dalam bisnis sehingga muncul produk revoluzio dan menjelaskan penerapan strategi STP produk Revoluzio pada PT Beon Intermedia. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan analisis deskriptif. Hasil penelitian menunjukkan bahwa faktor perubahan dalam bisnis sehingga muncul produk revoluzio antara lain 1)customer yang mengharapkan adanya extra value, experience, expert information, electronic solution, dan empowerment; 2)company;3)competition;4)collaboration;5) change. Sedangkan pada penerapan strategi STP, segmentation produk Revoluzio adalah pemilik bisnis pada usia 25 tahun atau lebih yang siap melakukan bisnis online di era digital marketing pada wilayah Indonesia dan Amerika Serikat, targeting produk Revoluzio adalah pelaku bisnis dan positioning produk Revoluzio adalah all in one digital business. Kata Kunci :Strategi pemasaran, e-business, digital marketing, Revoluzio